PENGARUH AKUNTABILITAS, MOTIVASI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA BATAM - Ramadani, Rifni; Effendi, Syahril (SCIENTIA JOURNAL, 2019)
Audit quality is something that cannot be separated from the auditor, because the results of his work can be assessed from the quality of the audit he provides. there are many factors in audit quality, including accountability, motivation and independence of an auditor. This study aims to examine whether these factors have a significant influence on audit quality. This study uses a simple random sampling method, by distributing questionnaires randomly to auditors in Batam City. this study has results that illustrate that Accountability, Motivation and Independence simultaneously have a significant influence on Audit Quality. Based on the f test of Accountability, Motivation and Independence on Audit Quality, it can be seen that Ho is rejected, Ha is accepted which means Accountability, Motivation and Independence together (simultaneous) have a significant effect on Audit Quality.